Dampak Kebijakan Pengeluaran Daerah terhadap Perubahan Struktur Tenaga Kerja di Provinsi Jawa Barat - Dirgantoro, Muhammad Arief (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2010)
The objectives of this research are: (1) to analyze labor structural change in West Java Province, (2) to analyze the impact of regional expenditure policies on labor structural change in West Java Province. In order to answer the above, a simultaneous equation model was established, consisting of 32 structural equations and 15 identity equations. Furthermore, this research used data pooling where data were analyzed with descriptive analysis, econometrics model, as well as predictions using a variety of policy scenario alternatives. The model was then estimated by a 2SLS method with SYSLIN procedures, while prediction simulation was performed by using SYMLIN procedures. In its development era, West Java Province experienced a transformation process on economy and labor. During process transformation, the decrease in the labor contribution of agriculture was not automatically followed by the increase in labor contribution to the industrial sector since it was absorbed by other sectors such as the informal ones. The result showed that the increasing development expenditure for infrastructure had a positive impact on labor growth and labor structural change on the agriculture sector, and it had lead to labor transformation.